2010
DOI: 10.1103/physrevb.81.212201
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of permanently densified silica: A Raman, Brillouin light, and x-ray scattering study

Abstract: Raman, Brillouin light, and x-ray scattering measurements have been carried out to characterize the low-frequency vibrational dynamics of the SiO(2) glass as function of its density. The obtained results demonstrate that while the distribution of the low-frequency states in the boson peak range is conserved under densification, these modes do not shift as a function of density as the acoustic modes do. The clear difference between the behavior of the vibrational states in the Boson peak range and that of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 38 publications
11
85
0
Order By: Relevance
“…It can been observed that I BP decreases with density, while ω BP increases with density. Both of these two trends (decrease of the intensity and increase of the frequency) have been observed experimentally in many system, such as in pure silica 80 , in lithium silicate glass 81 , in a Na 2 FeSi 3 O 8 glass 82 as well as in different polymers 83 .…”
Section: Boson Peakmentioning
confidence: 92%
“…It can been observed that I BP decreases with density, while ω BP increases with density. Both of these two trends (decrease of the intensity and increase of the frequency) have been observed experimentally in many system, such as in pure silica 80 , in lithium silicate glass 81 , in a Na 2 FeSi 3 O 8 glass 82 as well as in different polymers 83 .…”
Section: Boson Peakmentioning
confidence: 92%
“…In some systems, 14,18,19 it appears that the BP variation is solely associated with the change in the Debye frequency, which accounts for the modifications of the elastic continuum medium. In other cases, 13,[15][16][17] the BP shifts more strongly than suggested by the simple variation of the macroscopic medium. Specifically, this second behavior is observed when the system is subjected to an important volume change, of the order of 10% to 20%.…”
Section: Introductionmentioning
confidence: 96%
“…Among them we may recall the soft potential model, 4 the mode-coupling theory applied to the vibrations in glasses, 5 models on a lattice 6 or on the continuum 7 with randomly fluctuating elastic constants, and harmonic models where the atoms vibrate around topologically disordered configurations. 8,9 Experimentally the BP has been studied as a function of macroscopic parameters such as the temperature, 10,11 the density, [12][13][14][15] and the pressure 16,17 or during chemical vitrification 18 or as a function of the quenching rate. 19 It is observed that the BP shifts to higher frequencies and decreases in intensity when the pressure or the density is increased.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both theoretical and experimental studies assign the boson peak in glass to a phenomenon reminiscent of the van Hove singularity of the transverse phonon of the crystal counterpart [33,42,43]. It is worth mentioning that the boson peak has a dependence on the density of the material: as the density increases, the frequency of the boson peak increases and the height decreases [29][30][31]35,37,44]. Then, considering that the order parameter of the hypothetical LLT is just the density [9], the boson peak provides a good way to examine the existence of the LLT.…”
mentioning
confidence: 99%
“…Data were reduced by DAVE [26]. The boson peak is a broad peak observed at frequencies ∼2-10 meV in the inelastic neutron [27][28][29][30][31], nuclear inelastic [32][33][34][35], and Raman [36][37][38][39] scattering spectra of disordered materials and supercooled liquids. Its origin is widely believed to be related to the transverse dynamics of the material [32][33][34]40,41].…”
mentioning
confidence: 99%